PRINCIPLE AND CERTAIN NOMOTECHNICAL CHARACTERISTICS OF CRIMINAL OFFENCES AGAINST THE CONSTITUTIONAL ORDER AND SECURITY OF THE REPUBLIC OF SERBIA - Bodrožić, Ivana (The Policy of National Security, 2024)
The assessment of the legislative regulation of criminal offenses against constitutional order and security appears significant in the context of contemporary reflections on the possibilities that criminal law, as a socio-humanistic science, has or can have in the national security system of the Republic of Serbia. The author points out, through two separate units, general and particular nomotechnical characteristics of criminal acts against the constitutional order and security of the Republic of Serbia. The dogmatic, normative and logical method was dominantly used in the paper. Criminal law protection of the constitutional order and security of the Republic of Serbia is indisputable from the aspect of the basic postulates on which modern criminal law rests. The dually determined group protective object for this group of criminal acts is the constitutional order, on the one hand, and the security of the Republic of Serbia, on the other. Those are two abstract values, the fundamental social importance of which is extremely important for the standard realization of basic human and citizen rights as the most essential object of criminal law protection. As the security of the state and society are at the same time the objects to whose protection the activities of the national security policy are directed, it appears as important from a scientific point of view, the study of the character and scope of criminal law, which in this area should play a secondary role. In conclusion, the author assesses the criminal law protection of constitutional order and security as legitimate and rationally set and points out the importance that criminal justice as a social and humanistic science has and can have about priorities in the field of national security policy, pointing out at the same time that in the field of political crimes, criminal interventionism, which characterizes contemporary Serbian criminal law, has not come to the fore.
Keywords: criminal protection; political crimes; constitutional order and security; national security policy